2016
DOI: 10.1055/s-0042-101024
|View full text |Cite
|
Sign up to set email alerts
|

Antenatal Diagnosis of Dizygotic, Monochorionic Twins Following IVF/ICSI

Abstract: Abb. 1 Drei Embryonen im 6-bzw. 8-Zell-Stadium vor dem Embryotransfer (Kulturtag 3). Abb. 3 Sagittalschnitt des Körpers vom 1. Feten im Ultraschall mit Darstellung des Penis (siehe Pfeil). Abb. 4 Sagittalschnitt des Körpers vom 2. Feten im Ultraschall mit Darstellung der Klitoris (siehe Pfeil). Abb. 2 Bild der 1. Ultraschalluntersuchung in der 5 + 3 SSW zeigt eine Chorionhöhle mit 2 Dottersäcken.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Several studies have reported chimerism in tissues other than the blood (Fumoto et al, 2014;Rodriguez-Buritica et al, 2015;Korsun et al, 2016;Uysal et al, 2018). However, in this case, chimerism was only observed in blood cells and not in other tissues.…”
Section: Discussionmentioning
confidence: 60%
See 3 more Smart Citations
“…Several studies have reported chimerism in tissues other than the blood (Fumoto et al, 2014;Rodriguez-Buritica et al, 2015;Korsun et al, 2016;Uysal et al, 2018). However, in this case, chimerism was only observed in blood cells and not in other tissues.…”
Section: Discussionmentioning
confidence: 60%
“…An increasing number of MCDZ twins has been reported, and at least 80% of the reported cases were conceived by ART (Williams et al, 2004;Aoki et al, 2006;Ekelund et al, 2008;Parva et al, 2009;Assaf et al, 2010;Choi et al, 2013;Smeets et al, 2013;Lee et al, 2014a;Lee et al, 2014b;Fumoto et al, 2014;Korsun et al, 2016;Mayeur Le Bras et al, 2016). This indicates that when monochorionic twins, which originated from the transfer of two embryos, are diagnosed by ultrasound, we should consider two possibilities: the first possibility is that one embryo died and the other embryo developed to be monochorionic monozygotic (MCMZ), or alternatively, both embryos survive, share the placenta, and develop into MCDZ.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations